2008
DOI: 10.1080/00036840600749888
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate volatility and exports: a firm-level analysis

Abstract: The relationship between real exports and exchange rate volatility is investigated using panel data analysis at the firm level. Results indicate that there is no negative or positive relationship between volatility and real exports. In addition, firm size and level of international activity do not influence the size and significance of the volatility effect on exports. However, there is some evidence that firms use import revenue to lower their exchange rate exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Two recent studies have suggested that the negative trade effect of exchange rate variability is 'by no means a robust, universal finding' (Clark et al, 2004, p.6; see also Solakoglu, 2005). This MRA is able more conclusively to establish that the trade effects of exchange rate variability are highly conditional.…”
Section: Resultsmentioning
confidence: 52%
“…Two recent studies have suggested that the negative trade effect of exchange rate variability is 'by no means a robust, universal finding' (Clark et al, 2004, p.6; see also Solakoglu, 2005). This MRA is able more conclusively to establish that the trade effects of exchange rate variability are highly conditional.…”
Section: Resultsmentioning
confidence: 52%
“…Ozturk and Avaraci (2002) find a negative relationship between the exchange rate volatility and real exports of Turkey for 1989-2002 period. By using annual data at the firm level over 2001, Solakoglu et al, (2008 argue that there is no significant relationship between the exchange rate volatility and real exports of Turkey. Erdal et al, (2012) analyze the relationship between the exchange rate volatility and agricultural imports/exports of Turkey using the data from 1995 to 2007 period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gul and Ekinci (2006) argue that there isn't any causality from real exchange rate to neither import nor export of Turkey, but a unidirectional causality from export and import to the exchange rate. While Ozturk and Acaravci (2002) find a negative relationship between the exchange rate volatility and the real export flows of Turkey, Solakoglu et al (2008) claim that the exchange rate volatility has no significant effect on the real exports of Turkey. Erdem et al (2010) argue that agricultural trade is more related to exchange rate volatility than to the level of exchange rate and more importantly they emphasize that the effects of exchange rate and its volatility can be different for different agricultural commodities.…”
Section: Iiii Agricultural Subsidies/distortions and Agricultural Tmentioning
confidence: 99%